Tell Abraq during the second and first millennia BC: site layout, spatial organisation, and economy. (24th November 2017) - Magee, Peter; Händel, Marc; Karacic, Steven; Uerpmann, Margarethe; Uerpmann, Hans‐Peter
Abstract: Research recommenced at Tell Abraq in 2007, carried out by Bryn Mawr College with an international team in co‐operation with the Sharjah Archaeology Authority. Between 2007 and 2010 fieldwork was limited to documenting sections of the previous excavations and one small sounding while our attention focused mainly on the nearby shell‐midden site of Hamriya and the fortified Iron Age settlement site of Muweilah. Since 2010, large‐scale excavations have been conducted which have fundamentally altered our understanding of the layout of the settlement and its economic relations during the second and first millennia BC. In this report, we detail the results of this work and present preliminary interpretations.